Management accounting - Hutsalenko, L. V.; Kolesnikova, O. M.; Lepetan, I. M.; Marchuk, U. O.; Melyankova, L. V. (NULES of Ukraine, 2020)
The content of the tutorial corresponds to the curriculum of the discipline “Management Accounting”. The attention is paid to the general aspects of the organizational component and methods of management accounting. A separate section is devoted to the characteristics of management accounting in enterprises of agricultural sector of economy. The study material is supplemented with figures, tables and self-test questions. The tutorial will be useful for students, postgraduates and university teachers, as well as for accountants, auditors and entrepreneurs.
Recommended by the Academic Council of National University of Life and Environmental Sciences of Ukraine
Keywords: management; accounting; methods; agricultural sector